Working Together: Leveraging Teacher Study Groups to Improve Social and Emotional Learning in the Classroom. (April 2023) - Benner, Gregory J.; Rock, Marcia L.; Strycker, Lisa A.; Lee, Erica O.; Bailey, Pamela; Virgin, Ashley S.
Teachers of students with or at risk for emotional and behavioral disorders (EBD) may face obstacles and feel isolated when implementing social and emotional learning (SEL) programming with students. The teacher study group (TSG) offers an effective way to overcome barriers and improve SEL. These groups provide a gathering space for teachers to investigate problems of practice, celebrate points of pride, and strengthen professional learning in a focused area. In this article, we summarize existing research on SEL and TSGs and describe available SEL programs that incorporate TSGs. We provide an example of SEL-focused TSGs in practice, offering guidance and tips for early elementary school teachers—and the administrators who support them—who work with students with or at risk for EBD.